Controle penal da corrupção : limites e possibilidades do direito penal como forma de proteção da ordem econômica - Figueiredo, Vicente Cardoso de (2015)
This research aims to analyze the possibilities and the boundaries of application of criminal law for the protection of economic, specifically in the case of corrupt practices, due to the finding of corruption as widespread global phenomenon and negative effects on national and international markets. By addressing historical origins of corruption in Brazil and its current aspects, studies the international anti-corruption initiatives and their impact on the Brazilian legal system of control of corruption, seeing the economic order and social interest such as to protection through criminal law.